2021
DOI: 10.1038/s41419-021-03489-y
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CDKN2B-AS1 stabilized by IGF2BP3 drives the malignancy of renal clear cell carcinoma through epigenetically activating NUF2 transcription

Abstract: Because of the lack of sensitivity to radiotherapy and chemotherapy, therapeutic options for renal clear cell carcinoma (KIRC) are scarce. Long noncoding RNAs (lncRNAs) play crucial roles in the progression of cancer. However, their functional roles and upstream mechanisms in KIRC remain largely unknown. Exploring the functions of potential essential lncRNAs may lead to the discovery of novel targets for the diagnosis and treatment of KIRC. Here, according to the integrated analysis of RNA sequencing and survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…It is consistent with the previous other studies about its role in most cancers, which indicated that CDKN2B-AS1 exerted a pro-cancer effect [ 40–42 ]. For examples, in renal clear cell carcinoma, lncRNA CDKN2B-AS1 affected the malignancy through epigenetically activating NUF2 (NUF2 Component of NDC80 Kinetochore Complex) transcription [ 16 ]. Besides, CDKN2B-AS1 had a stimulative function in osteosarcoma and facilitates lung cancer development through their respective ways of regulation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is consistent with the previous other studies about its role in most cancers, which indicated that CDKN2B-AS1 exerted a pro-cancer effect [ 40–42 ]. For examples, in renal clear cell carcinoma, lncRNA CDKN2B-AS1 affected the malignancy through epigenetically activating NUF2 (NUF2 Component of NDC80 Kinetochore Complex) transcription [ 16 ]. Besides, CDKN2B-AS1 had a stimulative function in osteosarcoma and facilitates lung cancer development through their respective ways of regulation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA CDKN2B Antisense RNA 1 (CDKN2B-AS1) is located within the CDKN2B-CDKN2A (Cyclin Dependent Kinase Inhibitor 2B, Cyclin Dependent Kinase Inhibitor 2A) gene cluster at chromosome 9p21 [16]. It was reported that lncRNA CDKN2B-AS1 is associated with a number of pathologies, such as cardiovascular disease, Alzheimer's disease and type-2 diabetes [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…CDKN2B-AS1 is a multifunctional lncRNA that exerts carcinogenic effects in various tumors. In renal clear cell carcinoma, CDKN2B-AS1 exerts its carcinogenic activity by recruiting CREB-binding protein and three epigenetic modification complexes containing SET and MYND domains to the promoter region of the Ndc80 mitochondrial complex (NUF2) ( Xie et al, 2021 ). In lung cancer, CDKN2B-AS1 acts as a cavernous body by adsorbing miR-378b and regulating miR-378b/NR2C2 to promote cancer development ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of studies on IMPs describes their functional contexts, including mRNA transport (Eom et al, 2003;Farina et al, 2003;Kwon et al, 2002;Nielsen et al, 2001;Song et al, 2015), mRNA protection (Doyle et al, 1998;Jonson et al, 2014;Muller et al, 2018;Weidensdorfer et al, 2009), progression of various cancers (Doyle et al, 1998;Ioannidis et al, 2003Ioannidis et al, , 2005Liao et al, 2004;Wu et al, 2019), alternative splicing (Xueqing et al, 2020), diabetes and fatty acid metabolism (Regue et al, 2019), and m 6 A-methylation (Huang et al, 2018b). Other overview articles summarize these functions in an integrative (Bell et al, 2013;Degrauwe et al, 2016;Tong et al, 2018) or paralog-focused manner (Christiansen et al, 2009;Dai, 2020;Findeis-Hosey and Xu, 2012;Huang et al, 2018b;Lederer et al, 2014;Mancarella and Scotlandi, 2019;Wang et al, 2021;Xie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%